Two new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from South America - Lima, Lucas C. R. (2016)
Caenis Stephens, 1835 is a relatively diverse South American genus of Caenidae (Ephemeroptera), with 22 recorded spe-cies, but much of its diversity remains poorly explored in this region. In the present study, two new species of Caenis with apically pointed forceps are described: Caenis amacayacu sp. nov., based on male adults from Colombia; and C. elidioi sp. nov, based on all life stages from several localities in Brazil